Предмет: Алгебра,
автор: Stasja15
помогите пожалуйста решить полностью!!!
(х-1)(х²+8х+16)=6(х+4)
Ответы
Автор ответа:
0
(х-1)(х+4)(х+4)=6(х+4)
(Х-1)(х+4)=6
Х^2+4х-х-4-6=0
Х^2+3х-10=0
(Х+5)(х-2)=0
Х+5=0 х=-5
Х-2=0 х=2
Ответ: при х равном -5 и 2
(Х-1)(х+4)=6
Х^2+4х-х-4-6=0
Х^2+3х-10=0
(Х+5)(х-2)=0
Х+5=0 х=-5
Х-2=0 х=2
Ответ: при х равном -5 и 2
Похожие вопросы
Предмет: География,
автор: timurkakandzo
Предмет: Английский язык,
автор: altairzhumabek39
Предмет: Русский язык,
автор: isabaevabazarkul1
Предмет: Биология,
автор: 261818
Предмет: Физика,
автор: Ulyanaush2110